KRITIK ATAS KRITIK EPISTEMOLOGI TAFSIR M. ABIED AL JABIRI: Studi Kritis atas Madkhal ila al Quran al Karim - Fawaid, Ahmad (ULUL ALBAB Jurnal Studi Islam, 2015)
This paper critically views the epistemology of Muhammad Abid al Jabiri’s interpretation in his book, Madkhal ila al Quran al Karim. His latest work is projected to make the Quran relevant to mankind today and with certainly critiquing classical Quranic studies that have been constructed by previous scholars. Starting from Arab criticism, which is expected to synergize the gap between Turath and modernity, al Jabiri tried out his theory in the realm of Quranic studies oriented to maintain its originality and interpretation from sectarian influence. Focusing on al Jabiri’s review on the Quran, this paper examines and associates some of the problems with the epistemology of critique in Arab reasoning. Finally, it is inferred that the epistemologic offer of al Jabiri used in Turath is not fully applicable in Quranic studies for several reasons. First, the Quranic studies existed within the chain of sanad in its formation. Secondly, at the application stage, al Jabri often overlooked the sanad and narrations from the companions.